Upaya Meningkatkan Kemampuan Berbicara Anak Autisme Ringan di PL PDBK Semarang Dengan Media Smart Hippo Talk: Efforts to Improve the Speaking Ability of Children with Mild Autism at the Semarang PDBK PL Using Smart Hippo Talk Media - Aini, Durota Nurul; Arsanti, Meilan (Universitas Negeri Surabaya, 2025)
This research discusses about the use of Smart Hippo Talk as a speech theraphy medium to enhance the speaking skills of children with mild autism at PL PDBK Semarang. The research is using qualitative descriptive method with data obtained through observation, interviews, and documentation. The assessment of speaking abilities was based on the SCERTS model, which focuses on social communication, emotional regulation, and transactional support. The results indicated an improvement in both verbal and nonverbal communication after the use of Smart Hippo Talk. Participants showed increased eye contact, the ability to follow instructions, and began producing simple words and babbling. Additionally, the tool provided practical benefits for therapists by reducing the repetition of instructions through recorded voice features. These findings suggest that Smart Hippo Talk is a beneficial innovation to support speech therapy for children with mild autism.